أثر التدقيق الاجتماعي في تحسين ممارسة المسؤولية الاجتماعية - دراسة ميدانية بشركة قنعوبة للآجور بتقرت – - دبلة, فاتح; براهيمي, عثمان (جامعة الوادي - University of Eloued, 2022)
ملخص: تهدف هذه الدراسة إلى تبيان أثر التدقيق الاجتماعي في تحسين ممارسة المسؤولية الاجتماعية، وقد تم الاعتماد على المنهج الوصفي واستخدام الاستبانة كأداة لجمع البيانات، حيث شملت عينة البحث 40 عاملا من شركة قنعوبة للآجـــر بتقرت وقد تم التوصل إلى عدة نتائج أهمها: أنه يوجد أثر ذو دلالة إحصائية للتدقيق الاجتماعي في تحسين ممارسة البعد القانوني والبعد الأخلاقي والبعد الخيري للمسؤولية الاجتماعية، كما توصي الدراسة بضرورة تطبيق التدقيق الاجتماعي داخل المؤسسة واستغلال مخرجاته في إعداد أنشطة المسؤولية الاجتماعية بطريقة تضمن تحقيق توقعات أصحاب المصلحة. Abstract: The aim of this study is to signifies the impact of social auditing on improving the practice of social responsibility , and it was relied on the descriptive approach and the use of the questionnaire as a tool for collecting data , where the sample of the research sample 40 workers from the SARL BRIQUETERIE GANOUBA, and we reached many results, the most important of them is the effect of statistical significance of internal auditing in the legal principle and the ethical dimension of social events .Also, the study recommends on the importance of applying the social auditing inside the institution or the establishment and using its results in preparing social responsibility’s actions or projects in a way that ensures the achievement of the expectations of stakeholders.
The impact of social auditing on improving the practice of social responsibility. - A field study at the SARL BRIQUETERIE GANOUBA
Keywords: تدقيق اجتماعي ؛ مسؤولية اجتماعية.